2021
DOI: 10.1093/ptj/pzab048
|View full text |Cite
|
Sign up to set email alerts
|

Priorities of Hybrid Clinician-Managers: A Qualitative Study of How Managers Balance Clinical Quality Among Competing Responsibilities

Abstract: Objective Oversight of clinical quality is only one of physical therapy managers’ multiple responsibilities. With the move to value-based care, organizations need sound management to navigate this evolving reimbursement landscape. Previous research has not explored how competing priorities impact physical therapy managers’ oversight of clinical quality. The purpose of this study was to create a preliminary model of the competing priorities, motivations, and responsibilities of managers while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In a study of Australian physiotherapy managers, Glendinning (1987) found only 5% of their time was spent as spokesperson and 7% in the figurehead role. In a more contemporary study, Hoekstra et al (2021) noted hybrid PT clinician-managers felt a sense of personal responsibility to patients and staff. The findings of increased accountability are consistent with Hoekstra et al ’s (2021) findings, likely due to the more contemporary nature of Hoekstra et al ’s (2021) study.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a study of Australian physiotherapy managers, Glendinning (1987) found only 5% of their time was spent as spokesperson and 7% in the figurehead role. In a more contemporary study, Hoekstra et al (2021) noted hybrid PT clinician-managers felt a sense of personal responsibility to patients and staff. The findings of increased accountability are consistent with Hoekstra et al ’s (2021) findings, likely due to the more contemporary nature of Hoekstra et al ’s (2021) study.…”
Section: Discussionmentioning
confidence: 98%
“…Participants in this study also redefined success in their new roles. The hybrid PT clinician-managers studied by Hoekstra et al (2021) struggled to redefine measures of success, inferring quality based on operational metrics. Physical therapists in this study defined success at the team level through objective measures of patient satisfaction, outcomes and successful discharge planning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations